BIOETHICS IN THE CONTEXT OF MODERN SCIENCE - Dilorom Yuldasheva (American Journals Publishing, 2022)
In order to have a clearer idea of the essence of bioethics as a concept and a social phenomenon, it is necessary to consider the factors of its origin, to determine its place as a new scientific knowledge. A special place in this system is occupied by a complex of reasons related to modern scientific strategies, namely, with the fourth global scientific revolution, during which a new post-non-classical science is born. It is characterized by: the application of scientific knowledge in almost all spheres of social life, a revolution in the means of storing and obtaining knowledge, the growth of interdisciplinary and problem-oriented research not only in the socio-humanitarian, but also in the natural-technical (for example, predictive scenarios, social expertise, etc.) spheres. At the same time, comprehensive research programs are being implemented, where specialists from various fields of knowledge take part.
Keywords: bioethics, science, scientist, active participation in public and political life, socio-economic life, society, development.